KKN SISDAMAS: Analisis Pengelolaan Sampah Masyarakat Desa Bongas Kecamatan Cililin Kabupaten Bandung Barat - Ramadhani, Dian Hasna; Nurmutmainah, Nuni; Nurlaeli, Siti Dea (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Nvironment is still low. This is indicated by the fact that there is still a lot of garbage piled up in several places and on the sides of the road. Therefore it is necessary to carry out community empowerment activities for the cleanliness and health of the people of Bongas Village. The purpose of this activity is to increase the understanding and awareness of the people of Bongas Village about how important it is to keep the environment clean and to be able to encourage the community to consciously empower themselves. The implementation of activities to improve the clean and healthy quality of life for the people of Bongas Village through the SISDMAS Regular KKN program group 212 is carried out with steps consisting of preparation, implementation and evaluation of activities. The program that will be carried out in this activity is the mosque cleaning operation and mutual cooperation cleaning and ant operations. The planned activities have been realized by reducing waste on the side of the road, clean mosques. With this activity it is hoped that the people of Bongas Village can foster a more caring attitude and develop themselves in an effort to maintain the cleanliness and health of the community’s environment.